Functional fluvial landforms of the Pantanal: Hydrologic trends and responses to climate changes - Bergier, Ivan; Assine, Mario Luis [UNESP] (Elsevier, 2022)
Large-scale fluvial landforms emerge from iterative processes that sculpt Earth's surface. Tectonics, climate variability and erosion are major recurrent processes reshaping fluvial landforms ending up in self-affine patterns. In the case of the Pantanal, the largest wetland in South America, its depositional tract can be subdivided as fluvial megafans, interfans and the main trunk system. Here we provide an outlook of their origins by means of self-affine landforms and on the feedback of climate changes over landform functionalities. Climate variability modulates the magnitude of interannual fluvial discharge and sediment load from highlands to plains, affects groundwater recharge, as well as the subsidence and generation of accommodation in the depositional tract through river avulsion. Scenarios are envisaged by analyzing long-term summer rainfall intensity and the number of dry days in autumn/winter over the Upper Paraguay River Basin, and annual flood peaks measured at fluvial gauge stations in the Paraguay River at Ladário (Brazil) and Asunción (Paraguay). The frequency distributions of the annual flood peaks are found unimodal for Asunción and bimodal for Ladário, which suggests an unknown water supply at Asunción, likely from Pilcomayo River and Pantanal's groundwater. The latter might play a delayed role on Pantanal's hydrologic functioning at 20–40 years timescales. Besides the Paraguay River flood peaks, summer rainfall intensity and the number of dry days in autumn/winter are quasi-periodic at interannual and decadal scales. Cross-correlations analyses indicate a long-range memory between river floods and rainfall intensity, and 15–20 years lag between river floods and the number of dry days in drought seasons. Trends analysis suggests that summer rainfall intensity and the number of dry days in autumn/winter have been consistently increasing by about 0.6 mm/day/decade and 1 day/decade, respectively. Therefore, magnifications of fluvial discharge and sediment load at wet seasons and water deficits at drought seasons are anticipated. Such a scenario indicates extreme dry cycles over all self-affine functional landforms, particularly on abandoned lobes relying exclusively on rainwater, whereas extremes of rainfall intensity at rivers headwaters may amplify the risks of large-scale avulsions at active lobes of the fluvial megafans. In contrast, active lobes of megafans, interfans and the main trunk river system emerge as hotpots for wildlife refuge and ecosystem services.
Keywords: Conservation; Critical state; Droughts; Extreme events; River avulsion; Wetlands